Smarandache Multiplicative Function

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

SMARANDACHE MULTIPLICATIVE FUNCTION

Liu Yanni
Department of Mathematics, Northwest University, Xian, Shaanxi, P.R.China
Gao Peng
School of Economics and Management, Northwest University, Xian, Shaanxi, P.R.China
Abstract The main purpose of this paper is using the elementary method to study the
mean value properties of the Smarandache multiplicative function, and give an
interesting asymptotic formula for it.
Keywords: Smarandache multiplicative function; Mean Value; Asymptotic formula.
1. Introduction
For any positive integer n, we dene f(n) as a Smarandache multiplicative
function, if f(ab) = max(f(a), f(b)), (a, b) = 1. Now for any prime p and
any positive integer , we taking f(p

) = p. If n = p

1
1
p

2
2
p

k
k
is the
prime powers factorization of n, then
f(n) = max
1ik
{f(p

i
i
)} = max
1ik
{
i
p
i
}.
Now we dene P
d
(n) as another new arithmetical function. We let
P
d
(n) =

d|n
d = n
d(n)
2
, (1)
where d(n) =

d|n
1 is the Dirichlet divisor function.
It is clear that f(P
d
(n)) is a new Smarandache multiplicative function.
About the arithmetical properties of f(n), it seems that none had studied it
before. This function is very important, because it has many similar properties
with the Smarandache function S(n). The main purpose of this paper is to
study the mean value properties of f(P
d
(n)), and obtain an interesting mean
value formula for it. That is, we shall prove the following:
Theorem. For any real number x 2, we have the asymptotic formula

nx
f(P
d
(n)) =

4
72
x
2
lnx
+ C
x
2
ln
2
x
+ O
_
x
2
ln
3
x
_
,
104 SCIENTIA MAGNA VOL.1, NO.1
where C =
5
4
288
+
1
2

n=1
d(n) lnn
n
2
is a constant.
2. Proof of the Theorem
In this section, we shall complete the proof of the theorem. First we need
following one simple Lemma. For convenience, let n = p

1
1
p

2
2
p

k
k
be the
prime powers factorization of n, and P(n) be the greatest prime factor of n,
that is, P(n) = max
1ik
{p
i
}. Then we have
Lemma. For any positive integer n, if there exists P(n) such that P(n) >

n, then we have the identity


f(n) = P(n).
Proof. From the denition of P(n) and the condition P(n) >

n, we get
f(P(n)) = P(n). (2)
For other prime divisors p
i
of n (1 i k and p
i
= P(n)), we have
f(p

i
i
) =
i
p
i
.
Now we will debate the upper bound of f(p

i
i
) in three cases:
(I) If
i
= 1, then f(p
i
) = p
i


n.
(II) If
i
= 2, then f(p
2
i
) = 2p
i
2 n
1
4


n.
(III) If
i
3, then f(p

i
i
) =
i
p
i

i
n
1
2
i
n
1
2
i

ln n
ln p
i


n,
where we use the fact that
ln n
ln p
, if p

|n.
Combining (I)-(III), we can easily obtain
f(p

i
i
)

n. (3)
From (2) and (3), we deduce that
f(n) = max
1ik
{f(p

i
i
)} = f(P(n)) = P(n).
This completes the proof of Lemma.
Now we use the above Lemma to complete the proof of Theorem. First we
dene two sets A and B as following:
A = {n|n x, P(n)

n} and B = {n|n x, P(n) >

n}.
Using the Euler summation formula, we may get

nA
f(P
d
(n))

nA
P(n)d(n)

nx

xd(n) x
3
2
lnx. (4)
Smarandache multiplicative function 105
For another part of the summation, since P(n) = p, we can assume that
n = pl, where p > l and (p, l) = 1. Note that
P
d
(n) = n
d(n)
2
= (pl)
d(lp)
2
= (pl)
d(l)
and
f(P
d
(n)) = f((pl)
d(l)
) = f(p
d(l)
) = d(l)p,
we have

nB
f(P
d
(n)
=

plx
p>

pl
d(l)p =

plx
p>l
d(l)p =

px
p

l
x
p
l<p
d(l)
=

xpx
p

l<
x
p
d(l) +

p

x
p

l<p
d(l)
=

px
p

l<
x
p
d(l) + O
_
_

p

x
p

l<p
d(l)
_
_
+ O
_
_
_

x
p

l<
x
p
d(l)
_
_
_
=

p

x
p

l<
x
p
d(l) +

l

x
d(l)

p<
x
l
p
_
_

p

x
p
_
_
_
_

l

x
d(l)
_
_
+O
_
_
_

x
p

l<
x
p
d(l)
_
_
_+ O
_
_
_

x
p

l<
x
p
d(l)
_
_
_, (5)
where we have used Theorem 3.17 of [3]. Note that the asymptotic formula
(see Theorem 3.3 of [3])

nx
d(n) = xlnx + (2 1)x + O
_
x
_
xlnx, (2) =

2
6
(where is the Euler constant) and
(x) =
x
lnx
+
x
ln
2
x
+
2x
ln
3
x
+ O
_
x
ln
4
x
_
,
we have

px
p

l<
x
p
d(l) =

px
p
_
x
p
ln
x
p
+ (2 1)
x
p
+ O
__
x
p
__
x
3
2
(6)
106 SCIENTIA MAGNA VOL.1, NO.1

x
p

l<p
d(l)

x
p
2
lnp x
3
2
(7)

x
p

l<
x
p
d(l)

x
p
x
p
ln
x
p
x
3
2
. (8)
and
_
_

p

x
p
_
_
_
_

l

x
d(l)
_
_
x
3
2
(9)
Applying Abels identity (Theorem 4.2 of [3]) we also have

x
d(l)

p<
x
l
p =

l

x
d(l)
_
x
l
(
x
l
)
_ x
l
2
(y)dy
_
=

l

x
d(l)
_
1
2
x
2
l
2
ln
x
l
+
5
8
x
2
l
2
ln
2 x
l
+ O
_
x
2
l
2
ln
3
x
__
=

4
72
x
2
lnx
+ C
x
2
ln
2
x
+ O
_
x
2
ln
3
x
_
, (10)
where C =
5
4
288
+
1
2

n=1
d(n) lnn
n
2
is a constant.
Combining (5), (6), (7),(8),(9) and (10) we may immediately deduce the
asymptotic formula

nx
f(P
d
(n)) =

4
72
x
2
lnx
+ C
x
2
ln
2
x
+ O
_
x
2
ln
3
x
_
.
This completes the proof of Theorem.
Note. Substitute to

nx
d(n) = xlnx + (2 1)x + O
_
x
_
xlnx, (2) =

2
6
and
(x) =
x
lnx
+
x
ln
2
x
+
2x
ln
3
x
+ O
_
x
ln
4
x
_
,
we can get a more accurate asymptotic formula for

nx
f(P
d
(n)).
Smarandache multiplicative function 107
References
[1] F. Smarandache, Only Problems, Not Solutions, Xiquan Publishing House,
Chicago, 1993.
[2] Jozsef Sandor, On an generalization of the Smarandache function, Notes
Numb. Th. Discr. Math. 5 (1999), 41-51.
[3] Tom M. Apostol, Introduction to Analytic Number Theory, New York,
Springer-Verlag, 1976.

You might also like